Effect of foliar application with some marine algae and Licorice extracts on fruit quality of apple c.v starking delicious - رشيد خربوتلي; علي خليل ديب; هاديه إبراهيم (Latakia University Journal -Biological Sciences Series, 2022)
The research was carried out in Tartous Governorate, during the two growing seasons 2019-2020, on the 16 years old delicious Starking variety of apple trees, using foliar spraying with solid seaweed extracts (Alga600) of (2-4-6 g/l) and liquid seaweed extracts (Enkoseaweed) of (2-4-6 ml/l) concentrations, and licorice extract of (2-4- 8 ml/l) concentrations, beside basic ground fertilization. The results were the following: Foliar spray treatments improved the physical and chemical characteristics of fruits in general, treatment of the cultivar Starken Delicious with Enkoseaweed 6 ml/l outperformed other treatments in terms of: fruit weight = (173.2 g) ,fruit axis = (6.93 cm) compared with the control standard (158.7g, 6.08 cm) respectiviely, Mean while treatment with Algl600 6g/l outperformedother treatments in terms of :soluble solids percentage (13.17%) , total sugars percentage = (12.7%) , acidity percentage which was recorded (0.25%) , percentage of dry matter in fruit = (25.43%) ,the percentage of dry matter in the leaves = (45.88%) compared with the control standard (10.73, 9.8, 0.45,16.28,39.72%) respectiviely, and licorice extract 8 ml/l outperformed other treatments in terms of fruit size : (180.3 cm3) ,licorice extract outperformed other treatments in terms of fruit diameter = (6.33 cm) compared with the control standard (168.8cm3 5.72 cm) respectiviely.